Transition Pathways Toward the Prudent Use of Antimicrobials: The Case of Free-Range Broiler Farmers in France - Adam, Cécile J. M.; Fortané, Nicolas; Ducrot, Christian; Paul, Mathilde C. (Frontiers in Veterinary Science, 2020)
Reducing antimicrobial use (AMU) on farms is key to controlling the rise of resistant bacteria that have the potential capacity to infect humans via direct animal contact or via the food chain or the environment. To reduce AMU, antimicrobials must be used in a prudent and rational manner. Extensive efforts have been made recently to identify the cognitive and behavioral barriers to the appropriate use of antimicrobials by various livestock sector stakeholders. However, most studies carried out thus far have only partly captured the dynamic and systemic dimension of the processes involved in changes of practices related to AMU on farms. To shed light on the transition pathways implemented to reduce AMU, a qualitative study was conducted in France based on 28 semi-structured interviews with farmers, technicians and veterinarians from the free-range broiler production sector. Based on the thematic analysis of verbatims, we identified technical improvements which are key contributors to reduced AMU. We also highlighted some gaps in knowledge regarding AMU and antimicrobial resistance. We found that, rather than individual motivations alone, the extent to which farmers are embedded in collective organizations is decisive for changes in practices, and downstream operators (distributors and slaughterers) play a key role in the beginning of AMU transition pathways. As a result, we show that change in AMU requires a global rethinking of the overall socio-technical system rather than modifications of a single element in a farming system. Our results also highlight that transition pathways towards reduced AMU cannot just rely on trigger events, but also involves medium or long-term processes, with actors’ experiences and practices being modified on an incremental basis over time. Our study sheds light on the need for multi and trans-disciplinary research involving the social sciences to analyze interactions between stakeholders and the collective actions implemented to tackle the challenge of AMU reduction.